The Effect of Project-Based Learning on Critical Thinking Skills in Structural Engineering Courses: A Meta-analysis Study - Mahendra, Yoka; Triantho, Alex Irawan; Irawan, Ria Juwita (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2025)
This study aims to determine the influence of project-based learning on critical thinking skills in the Structural Engineering Course. This type of research is a meta-analysis research. The data sources in this study come from 13 national and international journals published in 2022-2025. Research data was obtained through the Mendeley database; Google Scholar; IEEE; and Sciencedirect. The data collection technique is direct observation through the database. Data analysis is statistical analysis with the help of the JASP application. The results of this study concluded that there was a significant influence of the project-based learning model on critical thinking skills in the Structural Engineering course with a high value of (d = 0.823; z = 7.826; p 0.001) in the effect size category. This finding provides important information for lecturers to encourage students' critical thinking skills in civil engineering lectures.ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh project based learning terhadap kemampuan beprikir kritis dalam Mata Kuliah Teknik Struktural. Jenis penelitian ini adalah penelitian meta-analisis. Sumber data dalam penelitian ini berasal dari 13 jurnal nasional dan internasional terbit tahun 2022-2025. Data penelitian diperoleh melalui database Mendeley; google scholar; IEEE; dan Sciencedirect. Teknik pengumpula data adalah observasi langsung melalui database. Analisis data adalah analisis statistic dengan bantuan aplikasi JASP. Hasil penelitian ini menyimpulkan bahwa adanya pengaruh signifikan model project based learning terhadap kemampuan berpikir kritis dalam mata kuliah Teknik Structural dengan nilai ( d = 0.823; z = 7.826; p 0.001) kategori effect size yang tinggi. Temuan ini memberikan informasi penting bagi dosen untuk mendorong kemampuan berpikir kritis siswa dalam perkuliahan Teknik sipil.